1990
DOI: 10.1111/j.1365-2923.1990.tb02452.x
|View full text |Cite
|
Sign up to set email alerts
|

Teaching quality assurance in Malaysia: a report on six workshops on quality assurance in patient care services for health care providers in government service

Abstract: In the government hospitals of Malaysia quality assurance activities have been introduced since 1985. Local clinicians and other health care workers had been stimulated by the Ministry of Health to pursue these activities, but they found themselves untrained and ill-prepared for the job. With the help of the World Health Organization a programme of training courses has been set up and conducted, most recently, in February 1989. A model for teaching quality assurance was developed, geared towards the needs of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Quality assurance activities have been introduced in Malaysian hospitals since 1985 in order to provide the best healthcare for the population ( Reerink & Alihussein, 1990 ). At that time, the MOH Malaysia set quality indicators to monitor the hospitals’ performance, and found that nurses and doctors are not trained to participate in the quality improvement programs ( Reerink & Alihussein, 1990 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quality assurance activities have been introduced in Malaysian hospitals since 1985 in order to provide the best healthcare for the population ( Reerink & Alihussein, 1990 ). At that time, the MOH Malaysia set quality indicators to monitor the hospitals’ performance, and found that nurses and doctors are not trained to participate in the quality improvement programs ( Reerink & Alihussein, 1990 ).…”
Section: Resultsmentioning
confidence: 99%
“…Quality assurance activities have been introduced in Malaysian hospitals since 1985 in order to provide the best healthcare for the population ( Reerink & Alihussein, 1990 ). At that time, the MOH Malaysia set quality indicators to monitor the hospitals’ performance, and found that nurses and doctors are not trained to participate in the quality improvement programs ( Reerink & Alihussein, 1990 ). The importance of improving quality of care and patient safety in Malaysian hospitals is visible in the growing attention to reduce medical errors, waste and inefficiency in the healthcare sector ( Husin, Rashid, & Othman, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Quality assurance activities have been introduced in Malaysian hospitals since 1985 in order to provide the best healthcare for the population. 1 At that time, the Ministry of Health Malaysia set quality indicators to monitor hospitals' performance and found that nurses and doctors were not trained to participate in the quality improvement programs. 2 The importance of improving quality of care and patient safety in Malaysian hospitals is visible in the growing attention to reduce medical errors, waste and ine ciency in the healthcare sector.…”
Section: Introductionmentioning
confidence: 99%
“…Optimizing the quality of services is possible within a given set of constraints, even when the highest priority is given to other considerations (Vuori, 1982). A number of less developed countries are moving from a strategy of health-service expansion to one that incorporates assurance of standards of health services (Amonoo-Lartson et al, 1985;Walker et al, 1988;Nicholas, 1989;Reerink and Alihussain, 1990).…”
Section: Introductionmentioning
confidence: 99%